Improving Ablation Safety for Hepatocellular Carcinoma Proximal to the Hilar Bile Ducts by Ultrasound-MR Fusion Imaging: A Preliminary Comparative Study - You, Yujia; Long, Yinglin; Yan, Ronghua; Luo, Liping; Zhang, Man; Li, Lu; Zeng, Qingjing; Li, Kai; Zheng, Rongqin; Xu, Erjiao (Frontiers in Oncology, 2021)
Aim: To explore whether ablation safety could be improved by ultrasound (US)-magnetic resonance (MR) fusion imaging for hepatocellular carcinoma (HCC) proximal to the hilar bile ducts (HBDs) through a preliminary comparative study. Methods: Between January 2010 and June 2019, 18 HCC nodules proximal to the HBDs were included in an US-MR fusion imaging-assisted radiofrequency ablation (RFA) group (study group), while 25 HCC nodules in a similar location were included as a control group. For the study group, the tumor and adjacent bile ducts were outlined on preprocedural MR images. Procedural ablation planning was conducted to assess the feasibility of ablating the tumors while avoiding biliary injury. Such tumors were then ablated under US-MR fusion imaging guidance. The control group nodules were ablated under conventional ultrasound guidance. Baseline characteristics and outcomes were compared between the groups. Results: After preprocedural assessment, 14 of 18 patients with tumors that were feasible to ablate underwent US-MR fusion imaging-assisted RFA. No biliary complications were observed in these 14 patients; the complication rate was significantly lower in the study group than in the RFA alone subgroup (30.8%, 4/13) of control group (P = 0.041). There was no significant difference in the technique efficacy rates (92.9% (13/14) versus 84.0% (21/25), P = 0.632) and local progression rates (7.1% (1/14) versus 4.0% (1/25), P = 1) between the study and control groups. Conclusions: US-MR fusion imaging may be a non-invasive means for assisting RFA of HCC nodules proximal to the HBDs and ensure ablation safety.